A New Insight into the Role of Calpains in Post-mortem Meat Tenderization in Domestic Animals A review - Lian, Ting (Asian-Australasian journal of animal sciences, 2013)
Tenderness is the most important meat quality trait, which is determined by intracellular environment and extracellular matrix. Particularly, specific protein degradation and protein modification can disrupt the architecture and integrity of muscle cells so that improves the meat tenderness. Endogenous proteolytic systems are responsible for modifying proteinases as well as the meat tenderization. Abundant evidence has testified that calpains (CAPNs) including calpain I (CAPN1) and calpastatin (CAST) have the closest relationship with tenderness in livestock. They are involved in a wide range of physiological processes including muscle growth and differentiation, pathological conditions and post-mortem meat aging. Whereas, Calpain3 (CAPN3) has been established as an important activating enzyme specifically expressed in livestock's skeletal muscle, but its role in domestic animals meat tenderization remains controversial. In this review, we summarize the role of CAPN1, calpain II (CAPN2) and CAST in post-mortem meat tenderization, and analyse the relationship between CAPN3 and tenderness in domestic animals. Besides, the possible mechanism affecting post-mortem meat aging and improving meat tenderization, and current possible causes responsible for divergence (whether CAPN3 contributes to animal meat tenderization or not) are inferred. Only the possible mechanism of CAPN3 in meat tenderization has been confirmed, while its exact role still needs to be studied further